UNCOVERING THE DOUAI FRAGMENT: COMPOSING POLYPHONY AND ENCODING A COMPOSER IN THE LATE FOURTEENTH CENTURY. (October 2021) - Louviot, Manon
Abstract : Douai, Bibliothèque Marceline Desbordes-Valmore, MS 1105/3 fragment 74.4/1 is a musical fragment from the second half of the fourteenth century, composed of two bifolios copied in black mensural notation. It not only contains a concordance for Multipliciter amando, a motet that, until now, has only survived in the famous Chantilly manuscript, but also four unica (another complete motet, two incomplete ones and a three-voice Gloria). After presenting a codicological overview of the fragment, I analyse distinctive features of each of the three complete pieces, based on the first modern transcription of the source. Special attention is given to the motet Ferre solet, which, by way of literary encoding mechanisms, reveals its composer's name (Frater Johannes Vavassoris) and its precise date of composition (1373), making these four folios a crucial witness for understanding fourteenth-century musical culture.